2020
DOI: 10.1101/2020.03.30.20044776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiology in the time of coronavirus: coping with the great wave

Abstract: Aims: To chart the effect of the COVID-19 pandemic on the activity of interventional electrophysiology services in affected regions. Methods: We reviewed the electrophysiology laboratory records in 3 affected cities: Wenzhou in China, Milan in Italy and London, United Kingdom. We interviewed electrophysiologists in each centre to gather information on the impact of the pandemic on working patterns and on the health of staff members. Results: There was a striking decline in interventional electrophysiology ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Additionally, patients eligible for ablation were older, mostly male, and presented with comorbidities (such as diabetes, hypertension or heart failure), which increased the risk for an unfavorable course of infection [8,10]. These data are consistent with our observations.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, patients eligible for ablation were older, mostly male, and presented with comorbidities (such as diabetes, hypertension or heart failure), which increased the risk for an unfavorable course of infection [8,10]. These data are consistent with our observations.…”
Section: Resultssupporting
confidence: 91%
“…The impact of the COVID-19 pandemic on the number of electrophysiological procedures varied across countries and regions, depending on the availability of hospital beds or necessary changes in healthcare management. Li et al [8] found a significant decrease in the number of electrophysiological procedures performed in various countries, which was related to the time of occurrence of the first wave of the disease. Based on Italian data, Boriani et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the prolongation of the pandemic and increasing recognition of the nonpulmonary complications of COVID‐19, such as cardiovascular disease, the need to return all health services of hospitals was felt. Among these, cardiac electrophysiological studies (EPSs) and implantation of intracardiac devices were significantly decreased during the COVID‐19 era; however, increased incidence of cardiac arrhythmias in COVID‐19‐infected patients, greater incidence of ischemic (because of delay for appropriate treatment) and nonischemic cardiomyopathies, and economic and social stress arising from quarantine rules are reasons why these procedures are necessary 5‐8 …”
Section: Introductionmentioning
confidence: 99%
“…The effects of lockdown period were explored in different contexts and terms: eating habits and lifestyle changes, 10 approaches implemented to support teleconsultations and management of AF and heart failure patients. 11,12 new-onset of arrhythmic events such as atrial fibrillation, 3 impact on interventional electrophysiology units routine and emergency work, 13 .…”
Section: Discussionmentioning
confidence: 99%